Uncertainties and controversies in axillary management of patients with breast cancer - Weber, Walter P.; Heil, Jörg (Cancer treatment reviews, 2023)
The aims of this Oncoplastic Breast Consortium and European Breast Cancer Research Association of Surgical Trialists initiative were to identify uncertainties and controversies in axillary management of early breast cancer and to recommend appropriate strategies to address them. ...